Answer: The corrected statement is A - B = -B + A.
Step-by-step explanation: Given that the subtraction of a matrix B may be considered as the addition of the matrix (-1)B.
We are given to check whether the commutative law of addition permit us to state that A - B = B - A.
If not, We are to correct the statement.
If the subtraction A - B is considered a the addition A + (-B), then the commutative law should be stated as follows :
A + (-B) = (-B) + A.
That is, A - B = -B + A.
Thus, the corrected statement is A - B = -B + A, not B - A.
P=2
Work:
<span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>+<span><span>−1</span><span>(<span><span>3p</span>+4</span>)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span>7p</span>+<span><span>−1</span><span>(<span>3p</span>)</span></span></span>+<span><span>(<span>−1</span>)</span><span>(4)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span><span>(<span>−2</span>)</span><span>(<span>2p</span>)</span></span>+<span><span>(<span>−2</span>)</span><span>(<span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span>−<span>4p</span></span>+2</span>+10</span></span><span><span><span>(<span><span>7p</span>+<span>−<span>3p</span></span></span>)</span>+<span>(<span>−4</span>)</span></span>=<span><span>(<span>−<span>4p</span></span>)</span>+<span>(<span>2+10</span>)</span></span></span><span><span><span>4p</span>+<span>−4</span></span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span>4p</span>−4</span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span><span>4p</span>−4</span>+<span>4p</span></span>=<span><span><span>−<span>4p</span></span>+12</span>+<span>4p</span></span></span><span><span><span>8p</span>−4</span>=12</span><span><span><span><span>8p</span>−4</span>+4</span>=<span>12+4</span></span><span><span>8p</span>=16</span><span><span><span><span><span>8p</span>8</span></span></span>=<span><span><span>168</span></span></span></span><span>p=<span>2
Hope this helps:)</span></span>
Answer:
y=3x+23 (lmk if you need me to explain)
Step-by-step explanation:
AB & CD
they have the same degree & are equally apart.